METODE NORMATIVE SURVEY DALAM ANALISA DAMPAK PENERAPAN KEGIATAN MBKM - Suryo Prakoso; Shabrina Sri Riswati; Muhammad Burhannudinnur; Sigit Rahmawan; Pantjanita Novi Hartami; Samsol Samsol; Mixsindo Korra Herdyanti; Cahaya Rosyidan; Onnie Ridaliani Prapansya; Havidh Pramadika; Ririn Yulianti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The Independent Campus Learning Program (MBKM) is a government program in an effort to provide opportunities for students from both public and private universities to study outside their study program. The opportunity is also wide open for students. This research is an analytical study of the implementation of MBKM competition activities in the Petroleum Engineering Study Program, FTKE Trisakti University. This study is supported by data obtained from the descriptive survey method (Normative Survey Method) of the entire academic community which includes the heads of the Faculties and Study Programs, lecturers, education staff and students as respondents. This study is intended to evaluate the impact of MBKM-based learning on lecturers and students, the availability and implementation of MBKM-based curriculum in Petroleum Engineering Study Program, Trisakti University and the level of satisfaction of lecturers, students and stakeholders on the availability of facilities and infrastructure to support the implementation of MBKM. The survey results show that MBKM activities have had a positive impact. Some of the challenges faced, among others, were the difficulty in getting partners to provide internship programs, technical constraints due to the pandemic, and program socialization that had not yet touched the entire academic community. More intensive efforts from Faculties and Study Programs to build cooperation with partners and update socialization methods are expected to improve the implementation of MBKM.